Emergent Photostability Synchronization in Coassembled Array Members for the Steady Multiple Discrimination of Explosives. Issue 2 (7th November 2021) - Cheng, Chuanqin; Cui, Linfeng; Xiong, Wei; Gong, Yanjun; Ji, Hongwei; Song, Wenjing; Zhao, Jincai; Che, Yanke
Abstract: The design of sensor array members with synchronous fluorescence and photostability is crucial to the reliable performance of sensor arrays in multiple detections and their service life. Herein, a strategy is reported for achieving synchronous fluorescence and photostability on two coassemblies fabricated from carbazole‐based energy donor hosts and a photostable energy acceptor. When a small number of the same energy acceptors are embedded into two carbazole‐based energy donor hosts, the excitation energy of the donors can be efficiently harvested by the acceptors through long‐range exciton migration and Förster resonance energy transfer (FRET) to achieve synchronous fluorescence and photostability in both coassemblies. More intriguingly, the synchronous photostability substantially improves the multiple discrimination capacity (e.g., 10 times more discriminations of TNT in two coassemblies have been achieved compared to the sensor array comprising two individual donor assemblies) and the working lifetime of the sensor array. The concept of optical synchronization (i.e., emission and photostability) of sensor array members can be extended to other sensor arrays for the steady multiple detection of certain hazardous chemicals. Abstract : Synchronized photostability and fluorescence enhancement in two coassemblies improve the multiple discrimination capacity of the resulting two‐member sensor array, as illustrated in the multiple detections of five classes of explosives.